Studies of IGF-I and Klotho Protein in Relation to Anabolic-Androgenic Steroid and Growth Hormone Administrations - Lehtihet, Mikael; Stephanou, Christina; Börjesson, Annica; Bhuiyan, Hasanuzzaman; Pohanka, Anton; Ekström, Lena (Frontiers in Sports and Active Living, 2022)
It has been suggested to longitudinally monitor Insulin-like growth factor I (IGF-I) as a biomarker for the detection of recombinant growth hormone (GH). Subsequently, it is of interest to understand any confounders of endogenous IGF-I. Herein we have studied if serum IGF-I concentration is affected by the intake of anabolic androgenic steroids (AAS) and the potential connection between IGF-I and klotho protein. Moreover, the usefulness of klotho as a biomarker for recombinant GH intake was assessed in healthy male volunteers. An ongoing administration of AAS did not affect the levels of IGF-I. Klotho protein was 30% higher in men with an ongoing AAS use compared to those with previous (>2 months ago) AAS use, and the serum klotho protein correlated negatively with luteinizing hormone (LH) (rs = −0.38, p = 0.04) and follicle stimulating hormone (FSH) (rs = −0.35, p = 0.05) levels. Serum IGF-I and klotho concentrations showed no correlation in the AAS using population but showed a strong negative correlation in healthy volunteers (rs = −0.86, p = 0.006). The intake of recombinant GH did not affect the serum concentrations of the klotho levels. In conclusion, IGF-I was not affected by supra-physiological AAS doses in men. Interestingly, an association between AAS intake and serum klotho was seen. The usefulness of klotho as an androgen biomarker warrants further studies, whereas klotho can be discarded as a promising biomarker for GH doping.